2012
DOI: 10.1089/pho.2012.3252
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Evaluation of the Efficacy of Diode Laser as an Adjunct to Mechanical Debridement Versus Conventional Mechanical Debridement in Periodontal Flap Surgery: A Clinical and Microbiological Study

Abstract: The bactericidal effect of the diode laser was clearly evident by greater reduction of CFU of obligate anaerobes in the test group than in the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(72 citation statements)
references
References 33 publications
5
61
1
1
Order By: Relevance
“…Positive results of microbial using the same type of DL [25] . Its verified the lethal effect of DL radiation on MOs associated with periodontitis [28] .…”
Section: IIImentioning
confidence: 66%
See 2 more Smart Citations
“…Positive results of microbial using the same type of DL [25] . Its verified the lethal effect of DL radiation on MOs associated with periodontitis [28] .…”
Section: IIImentioning
confidence: 66%
“…Its advantages, include a bloodless operating field, minimal swelling and scarring, and much less or no postsurgical pain. When its surgical procedures are carried out, the surface produced heals favorably as an open wound, without need for sutures or surgical dressings, verified the lethal effect of DL associated with dental periodontitis [28] . That results showed at the end of the treatment period the CFUs/ml were 3%=15 for SG and 33%=165 for CG, so that had appeared the significant different between treatment method and healing pathway by reducing the CFUs/ml in SG more than and CG by different in CFUs/ml as 30%=150MOs, that had indicated the DL therapy is more effective and takes short healing time with its beneficially in reducing CFUs/ml during the treatment of chronic periodontitis other than the old or surgical treatment methods.…”
Section: IIImentioning
confidence: 85%
See 1 more Smart Citation
“…So in order to set these parameters that demonstrated that high intensity DL (1.4 W/30 s) did not cause any signs of thermal effects such as charring, necrosis or fusion on the root which inferred about the angle of Laser beam, time and power irradiation on gingival fibroblasts. Other characteristics about this Laser were taken into account in order to use in dental practice: it is one of the cheaper high intensity Laser; furthermore DL machine used in this research is small and light, therefore portable Lasers, as a group, have inconsistently demonstrated the ability to reduce microorganisms within a periodontal pocket [13][14] . Nonsurgical mechanical therapy alone may not effectively eliminate the periodontal disease completely, particularly in deep pockets.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of the conventional therapy have probed us to implement the use of adjunctive antimicrobial measures. Laser-assisted periodontal therapy has attracted attention recently as a potential alternative or adjunct to conventional mechanical debridement [14] . CO 2 laser, Neodymium-doped: Yttrium-Aluminum-Garnet (Nd:YAG) Laser, and DL and Erbium-doped:YttriumAluminium-Garnet (Er:YAG) Laser have A part of Laser energy scatters and penetrates during irradiation into periodontal pockets.…”
Section: Introductionmentioning
confidence: 99%